The water mites of the family Hygrobatidae (Acari, Hydrachnidia) in Italy - Gerecke, Reinhard (Zootaxa, 2021)
Based on field work mostly done in the late 20th century, a survey is given on the diversity and distribution of spring- and stream-dwelling water mites of the family Hygrobatidae in Italy. Five species, all representatives of the subgenus Atractides Koch, 1837 s. str., are described as new to science: Atractides asinus sp. nov., A. castor sp. nov., A. cydonius sp. nov., A. dinisi sp. nov., and A. pollux sp. nov.. A further 13 species are recorded for the first time from Italy: Atractides anellatus Lundblad, 1956, A. asticae Petrova, 1968, A. denticulatus Walter, 1947, A. fissus (Walter, 1927), A. fluviatilis (Szalay, 1929), A. glandulosus (Walter, 1918), A. graecus K. Viets, 1950, A. lunipes Lundblad, 1956, A. remotus Szalay, 1953, A. subterraneus (K. Viets, 1932), Hygrobates arenarius Smit & Pešić, 2017, H. setosus Besseling, 1942, and H. cf. turcicus Pešić, Esen & Dabert, 2017. In summary, a total number of 66 hygrobatid species is now known from the area treated. Previous records of Atractides allgaier Gerecke, 2003 from Corsica and Sardinia, and of A. lunipes Lundblad, 1956 from Corsica, refer to A. castor sp. nov., resp. A. corsicus E. Angelier, 1954. Redescriptions are given for seven remarkable and/or incompletely documented species: Atractides asticae, A. fluviatilis, A. graecus, A. inflatipalpis K. Viets, 1950, A. lunipes, A. protendens K.O. Viets, 1955, and A. remotus. Problems concerning diagnostic features are discussed for several species. Atractides fluviatilis, A. valencianus K. Viets, 1930 and A. inflatipalpis, along with two species not recorded from Italy, namely A. algeriensis (Lundblad, 1942) and A. stancovici Pešić & Gerecke, 2010, are summed up in a “fluviatilis species group”. Within this clade, several species tend to grade into each other morphologically, and females cannot be classified with certainty.